Spatial variability of CO2 emission, temperature and soil moisture in an area under pasture in the Amazon region, Brazil - Silva, Diogo André Pinheiro da; Campos, Milton César Costa; Mantovanelli, Bruno Campos; Santos, Luís Antônio Coutrim dos; Soares, Marcelo Dayron Rodrigues; Cunha, José Mauricio da (Revista de Ciências Agroveterinárias, 2019)
Knowledge of the spatial distribution of temperature, soil moisture and CO2 emissions is essential to understand the soil as a source or drainage of CO2, as changes in use and management influence this dynamic. This study aimed to investigate the temperature, soil moisture and CO2 emissions in an area under pasture in Humaitá, AM. An area was demarcated at 70 x 70 m, with regular spacing of 10 m, totaling 64 points, measurements were carried out in both the rainy and dry season. CO2 emissions and soil temperature were recorded using portable flow chamber and temperature sensor LI-COR system (LI-8100). Moisture was assessed using portable system TDR, with subsequent descriptive statistical and geostatistical analysis. The pasture had higher emission of soil CO2 in the first collection period, characterized as rainy season. Spatial variations of CO2 emissions are closely related to climatic variables between dry and rainy periods.